2012
DOI: 10.1148/radiol.12112350
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognostic Value of Different Components of Coronary Atherosclerotic Plaque at Cardiac CT Angiography beyond Coronary Calcification in Patients with Acute Chest Pain

Abstract: The strong prognostic value of cardiac CT angiography is incremental to its known diagnostic value in patients with acute chest pain without ACS and is independent of traditional risk factors and CAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…Indeed, most acute events, such as MI, appear to occur at sites of relatively modest sized plaques (494) or plaques poorly visualized by conventional angiography (44). However, these considerations should not overshadow the fact that accurate assessment of total plaque burden, as with coronary CT angiography, provides almost complete separation of future risk of coronary events ranging from near zero for no detectable plaque to extremely high risk for extensive plaque (689,1281). Such scoring also predicts all-cause mortality (320).…”
Section: Overview Of Atherogenesismentioning
confidence: 99%
“…Indeed, most acute events, such as MI, appear to occur at sites of relatively modest sized plaques (494) or plaques poorly visualized by conventional angiography (44). However, these considerations should not overshadow the fact that accurate assessment of total plaque burden, as with coronary CT angiography, provides almost complete separation of future risk of coronary events ranging from near zero for no detectable plaque to extremely high risk for extensive plaque (689,1281). Such scoring also predicts all-cause mortality (320).…”
Section: Overview Of Atherogenesismentioning
confidence: 99%
“…In studies that investigated the prognostic value of cardiac CTA, coronary artery stenosis and great plaque burden were stronger predictors of future cardiovascular events than were routine clinical predictors, exercise stress test results, or the CACS in patients without known CAD (36,37). Similarly, in studies of outpatients at low to intermediate risk, coronary artery stenosis severity, the presence of noncalcified and/or mixed plaque, and multivessel involvement were superior to traditional risk factors, including the CACS, for predicting CAD (11,38).…”
Section: Resultsmentioning
confidence: 93%
“…In the current study, we used cardiac CTA to screen for subclinical CAD in patients with newly diagnosed T2D who had at least one cardiovascular risk factor. Advanced CT techniques, such as 64-slice cardiac CTA, can measure the degree of stenosis with high diagnostic accuracy and can provide details about plaque composition, including whether the plaque is noncalcified or mixed and rupture prone (11). In studies that investigated the prognostic value of cardiac CTA, coronary artery stenosis and great plaque burden were stronger predictors of future cardiovascular events than were routine clinical predictors, exercise stress test results, or the CACS in patients without known CAD (36,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study that focused on the female HIV population found that young, asymptomatic HIV-infected women also demonstrate increased NCAP [15]. This has led to a surge in interest in the association between HIV infection and CVD, specifically NCAP due to the increase of major adverse cardiac events (MACE) associated with it [16]. It should be pointed out that the coronary plaque analysis from the MACS database was concluded using cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%